The Rainbow in the School: in the public recognition of the cultural diversities in inclusive school - Resende, José Manuel (2021)
Professionals of two schools, one in Portugal and the other in Brazil, were investigated regarding school inclusion and their considerations on multiple cultural indexes in their institutions. How do these cultural manifestations coexist in the schooling process? How are they manifested when confronted by the diverse public enrolled in their school, and how do they analyze this coexistence in school activities? How do they include the tangible sides of the plural cultural expressions in their in the learning? Based on the issues raised by those professionals, the article shows how concepts of multiculturalism, interculturality, and cultural diversity are reframed in the main policies and public actions both in Brazil and Portugal. From this analytical perspective, it proposes the observation of these policies and actions are interpreted by the two groups. The study expands the discussion those concepts to controversies raised by scientists in the education field regarding public intentions manifested by those that have ruled education in these two countries.